Supratrochlear artery pseudoaneurysm: A rare complication of skin flap surgery - Ana Paula Bald; Fernando Figueiredo Kopke; Ariel Córdova Rosa; Telma Sakuno; Athos Paulo Santos Martini (Sociedade Brasileira de Dermatologia (SBD), 2024)
Arterial pseudoaneurysm is a rare complication caused by damage to the arterial wall, resulting in a locally confined hematoma connected to the lumen of the artery. We report the case of a patient on anticoagulants who developed nodules at the surgical wound site after Mohs micrographic surgery for basal cell carcinoma. The initial clinical suspicion was the formation of a simple hematoma. However, Doppler ultrasound examination revealed the presence of pseudoaneurysms in the bilateral supratrochlear arteries. We believe this is the first reported case of supratrochlear artery pseudoaneurysm following dermatologic surgery.